Major Climate Variabilities and the Associated Interbasin Relationships Predicted by the APCC In‐House Model - Seon Tae Kim; Ji‐Hyun Oh; Yun‐Young Lee; WonMoo Kim; A‐Young Lim (Earth and Space Science, 2019)
Abstract In this study, a series of analyses were performed to verify the performance of the current Asia‐Pacific Economic Cooperation Climate Center (APCC) in‐house model, the Seamless Coupled Prediction System (SCoPS), for predicting major climate variabilities and the related dynamical processes. The prediction skills for forecasting the major atmospheric and oceanic climate modes and the related circulation patterns in the tropical Pacific, Indian, and Atlantic Oceans were examined. The interbasin relationships between the major modes were also analyzed. Despite slight spatial and temporal shifts, SCoPS simulates the atmospheric responses to the El Niño–Southern Oscillation (ENSO) well over both the tropical and the northwestern Pacific. The major modes over the Indian Ocean are also reasonably well predicted. The dynamical interaction between the Indian and Pacific Oceans, which is involved in the development of the tropical Pacific modes, is also represented with good accuracy. In case of the Atlantic Ocean, the northern tropical sea surface temperature (SST) variability is better predicted than the southern tropical SST variability. Through examining the characteristics of El Niño‐La Niña asymmetries in forcing the tropical Atlantic variability SST modes, we found that this skill difference could be partly because of too strong linear response of the SST variability in the southern region to ENSO. The North Atlantic Oscillation, one of the major atmospheric modes during boreal winter, was also investigated. It was found that SCoPS reasonably replicates the observed loading pattern and temporal variation but tends to overestimate the relationship between North Atlantic Oscillation and ENSO.